THE ROLE OF SEAFARING EXPERIENCE IN ENHANCING SUSTAINABILITY EDUCATION IN MARITIME VOCATIONAL TRAINING - Alamsyah, Jaya (Faculty of Administrative Science, Universitas Brawijaya, 2025)
The growing emphasis on sustainability in the maritime industry necessitates effective integration of sustainability education into maritime vocational training curricula. This study examines how seafaring experience enhances sustainability instruction, addressing gaps in the practical application of sustainability concepts. Previous research has focused on theoretical sustainability education, yet limited studies have explored the role of experiential learning from seafaring professionals. The study aims to determine how maritime lecturers with seafaring experience influence sustainability teaching effectiveness and assess whether graduates feel adequately prepared for industry sustainability challenges. Using a qualitative research approach, the study employed semi-structured interviews and focus groups with maritime experts, lecturers, and graduates. Thematic analysis categorized findings into competency development, sustainability awareness, and real-world application of sustainability principles. Results reveal a high overall effectiveness score of 9/10, with seafaring-experienced lecturers scoring 9.3/10 in integrating sustainability into teaching. However, graduate preparedness scored lower (8.8/10), highlighting the need for more hands-on sustainability training. The study concludes that structured experiential learning, industry collaborations, and sustainability-focused faculty development programs are essential for bridging the gap between theoretical instruction and real-world sustainability applications. These findings provide practical insights for maritime institutions, policymakers, and educators, ensuring that future maritime professionals are equipped with both theoretical knowledge and applied sustainability skills to meet evolving industry demands.